The Presence of a Mobile Phone Does Not (Necessarily) Change the Fundamental Processes of Face-to-Face Relational Conflict - Roaché, David; Caughlin, John; Wang, Ningxin; Pusateri, Kimberly (Human Communication & Technology, 2020)
This study extends research examining the presence of mobile phones during interpersonal interactions into the context of serial arguments between dating couples. Fifty-eight dating couples (N = 116) had two 10-minute face-to-face serial argument conversations in a laboratory-controlled experiment when technology was either present or absent. The most salient findings were consistent with longstanding findings in the conflict literature: positive communication was associated positively with desirable outcomes (conversational satisfaction, perceived resolvability, and conversation effectiveness) whereas negative behaviors were inversely related to desirable conflict outcomes. Overall, results showed little evidence that the presence of a participant’s smartphone affected the quality of serial argument conversations, but biological sex moderated the impact of technology on conversation satisfaction and perceived conversation effectiveness, such that technology presence negatively impacted women more than men. These findings suggest that the presence of mobile phones does not fundamentally alter effective conflict engagement in general, but there are likely circumstances in which the presence of mobile phones is important.